El cambio del discurso histórico de la CONAIE, a la luz de las protestas de octubre de 2019 - Valverde Fraija, Gabina Dayanna (2020)
This paper explores discursive changes of the Confederation of Indigenous Nationalities of Ecuador (CONAIE), during the cycle of protests of October 2019, and contrasts the approaches of this period with those that animated the historical struggle of the indigenous cause in Ecuador. That is why it seeks to evaluate the impact of the events of October on the historical discourse of the indigenous movement, and to what extent this change led to divisions within CONAIE, as well as the effects that this turn of the discourse caused on the relations between indigenous people and mestizo population of Ecuador. This qualitative research is carried out within the framework of the situational analysis of the case, from a political perspective.